Bactericidal Disruption of Magnesium Metallostasis in Mycobacterium tuberculosis Is Counteracted by Mutations in the Metal Ion Transporter CorA - Landys Lopez Quezada (American Society for Microbiology, 2019)
ABSTRACT A defining characteristic of treating tuberculosis is the need for prolonged administration of multiple drugs. This may be due in part to subpopulations of slowly replicating or nonreplicating Mycobacterium tuberculosis bacilli exhibiting phenotypic tolerance to most antibiotics in the standard treatment regimen. Confounding this problem is the increasing incidence of heritable multidrug-resistant M. tuberculosis. A search for new antimycobacterial chemical scaffolds that can kill phenotypically drug-tolerant mycobacteria uncovered tricyclic 4-hydroxyquinolines and a barbituric acid derivative with mycobactericidal activity against both replicating and nonreplicating M. tuberculosis. Both families of compounds depleted M. tuberculosis of intrabacterial magnesium. Complete or partial resistance to both chemotypes arose from mutations in the putative mycobacterial Mg2+/Co2+ ion channel, CorA. Excess extracellular Mg2+, but not other divalent cations, diminished the compounds’ cidality against replicating M. tuberculosis. These findings establish depletion of intrabacterial magnesium as an antimicrobial mechanism of action and show that M. tuberculosis magnesium homeostasis is vulnerable to disruption by structurally diverse, nonchelating, drug-like compounds. IMPORTANCE Antimycobacterial agents might shorten the course of treatment by reducing the number of phenotypically tolerant bacteria if they could kill M. tuberculosis in diverse metabolic states. Here we report two chemically disparate classes of agents that kill M. tuberculosis both when it is replicating and when it is not. Under replicating conditions, the tricyclic 4-hydroxyquinolines and a barbituric acid analogue deplete intrabacterial magnesium as a mechanism of action, and for both compounds, mutations in CorA, a putative Mg2+/Co2+ transporter, conferred resistance to the compounds when M. tuberculosis was under replicating conditions but not under nonreplicating conditions, illustrating that a given compound can kill M. tuberculosis in different metabolic states by disparate mechanisms. Targeting magnesium metallostasis represents a previously undescribed antimycobacterial mode of action that might cripple M. tuberculosis in a Mg2+-deficient intraphagosomal environment of macrophages.